2015
DOI: 10.1007/s00345-015-1598-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for recurrence probabilities after intravesical chemotherapy in patients with intermediate-risk non-muscle-invasive bladder cancer, including external validation

Abstract: PurposeTo develop a model to predict recurrence for patients with intermediate-risk (IR) non-muscle-invasive bladder cancer (NMIBC) treated with intravesical chemotherapy which can be challenging because of the heterogeneous characteristics of these patients.MethodsData from three Dutch trials were combined. Patients treated with intravesical chemotherapy with characteristics according to the IR definition of the EAU guideline 2013 were included. Uni- and multivariable Cox regression with selection methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…Attempts have been made by many researchers to improve the algorithms developed by the EORTC. Some authors have focused on the preparation of prognostic models for specific groups of patients, while others have attempted to determine the probability of tumor recurrence by evaluating gene polymorphisms, inflammation, or the presence of tumor markers in urine (Ieda et al 2016;Kim et al 2016;Maturana et al 2016;Chen et al 2012;Cui et al 2017;Todenhöfer et al 2014;Lammers et al 2016). The possibility of improving the accuracy of these algorithms by means of immunohistochemistry was also analyzed (Ding et al 2014;Passoni et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made by many researchers to improve the algorithms developed by the EORTC. Some authors have focused on the preparation of prognostic models for specific groups of patients, while others have attempted to determine the probability of tumor recurrence by evaluating gene polymorphisms, inflammation, or the presence of tumor markers in urine (Ieda et al 2016;Kim et al 2016;Maturana et al 2016;Chen et al 2012;Cui et al 2017;Todenhöfer et al 2014;Lammers et al 2016). The possibility of improving the accuracy of these algorithms by means of immunohistochemistry was also analyzed (Ding et al 2014;Passoni et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate Risk (IR)-NMIBC has a critical threshold when urologists choose intravesical chemotherapy protocol, either SI or maintanance therapy. Lammers et al [28] reported a risk tablefor IR-NMIBC patients treated with intravesical chemotherapy including five relevant predictors of reccurence-free survival: history of recurrences, history of intravesical treatment, grade 2, multiple tumors and adjuvant treatment with epi-rubicin. These individual predictors were used to subdivide IR patients into three risk groups, which is related to recurrence outcome.…”
Section: Predictive Markers Of Nmibcmentioning
confidence: 99%
“…The urologist together with the patient can choose for an individualized treatment approach. [28] However, further chemotherapy instillations after SI improved recurrence-free survival in intermediate-risk patients. [29] The available evidence does not support treatment longer than one year of intravesical chemotherapy (LE: 3).…”
Section: Predictive Markers Of Nmibcmentioning
confidence: 99%
“…However, the sensitivities of NMP22 and BTA are 32-92% and 53-89%, respectively, and their specificities are 51-94% and 53-89%, respectively. (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) Furthermore, BTA and NMP22 yield a high pseudopositive ratio for hematuria, urinary infections, and urolithiasis patients; therefore, these tests are not used routinely for diagnosis of NMIUC. (2,11) Thus, development of new tumor markers for UC that can also replace cystoscopy for routine monitoring examination is desirable.Ln-c2, a component of (17) is an interesting candidate tumor biomarker, as it is expressed in cancerous tissues.…”
mentioning
confidence: 99%